Solid lipid nanoparticles and nanostructured lipid carriers as novel drug delivery systems: applications, advantages and disadvantages - Parisa Ghasemiyeh; Soliman Mohammadi-Samani (Wolters Kluwer Medknow Publications, 2018)
During the recent years, more attentions have been focused on lipid base drug delivery system to overcome some limitations of conventional formulations. Among these delivery systems solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) are promising delivery systems due to the ease of manufacturing processes, scale up capability, biocompatibility, and also biodegradability of formulation constituents and many other advantages which could be related to specific route of administration or nature of the materials are to be loaded to these delivery systems. The aim of this article is to review the advantages and limitations of these delivery systems based on the route of administration and to emphasis the effectiveness of such formulations.